The Unruly Island: colonialism's predicament in late nineteenth-century East Timor - Roque, Ricardo (2012)
This paper describes the state of colonial administration in East Timor in the late nineteenth century. It explores a common view of the “underdeveloped” nature of nineteenth-century Portuguese colonialism by examining the recurrent complaints made by the Portuguese governors about East Timor’s miserable and unmanageable colonial condition. From the civilizing perspective, Portuguese rule in Timor seemed virtually impossible. The island was geographically isolated from Macau and Lisbon; the administration was militarily weak, economically poor, and enmeshed in multiple political conflicts, either between the colonizers and the indigenous or amongst colonizers. Yet this paper also tries to go beyond the negative connotations and the Eurocentric character of such discourses. In contrast, it suggests a productive engagement with the predicament of colonial administration. The intention is to set forth an alternative hypothesis that emphasizes the tactical character of colonialism and its embedding in the pragmatics of local colonial interactions.